Impact of Preoperative and Intraoperative Factors in Cataract Surgery - Pérez-Campagne, E.; Basdekidou, C.; Petropoulos, I. K.; Noachovitch, B.; Moubri, M. (Klinische Monatsblätter für Augenheilkunde, 2013)
Background: Cataract surgery is the most common procedure in ophthalmology. However the surgical outcome depends on various factors. The impact of preoperative and intraoperative factors on the surgical procedure were investigated.Patients and Methods: Prospective consecutive study of eyes that underwent cataract surgery. The studied parameters included: age, body mass index (BMI), medical history, type of anaesthesia, preoperative patientʼs anxiety level (scale from 0 to 10), spherical equivalent (SE), keratometry, axial length (AL), time and percentage of ultrasounds (US), intraoperative complications, duration of surgery. The eyes were separated into two groups: the “no complication group” and the “complication group”.Results: 529 eyes were included. Age averaged 75.5 years old (44; 100), mean BMI (kg/m2) was 26.3 (13.7; 45.2), patients had cardiovascular history in 61.05 % of cases, the type of anaesthesia used was topical in 93.4 %, subtenon in 4.7 % and general in 1.9 % of cases. Mean preoperative anxiety was 4.04 (0; 10), mean preoperative SE was − 0.12 (− 10; 7.5), mean keratometry (diopters) was 43.88 (39.5; 49), mean AL (mm) was 23.29 (20.91; 29.78), mean time of US (minutes) was 1.89 (0.08; 9.2), mean percentage of US was 10.5 (2; 30) and mean surgical duration (minutes) was 17.15 (5; 50). There was a statistically significant difference (p < 0.0001 in all cases) between both groups in the preoperative anxiety, the time of US and the duration of surgery. The “complication group” had higher scores in all cases as well as more proportion of patients with cardiovascular history. There was no statistically significant difference between both groups for the BMI, SE, AL, keratometry and percentage of US.Conclusions: The preoperative anxiety level and a cardiovascular medical history together with a prolonged time of US and a longer surgical duration seem to provide more complications during the surgery. The BMI, SE, AL and keratometry did not influence the surgical procedure.
Keywords: risk factor; cataract surgery; phacoemulsification; spherical equivalent; axial length; keratometry; anaesthesia; anxiety; ultrasound; outcomes